Host antitumor resistance improved by the macrophage polarization in a chimera model of patients with HCC. (3rd April 2017) - Asai, Akira; Tsuchimoto, Yusuke; Ohama, Hideko; Fukunishi, Shinya; Tsuda, Yasuhiro; Kobayashi, Makiko; Higuchi, Kazuhide; Suzuki, Fujio
ABSTRACT: Despite major advances in curative and palliative approaches, hepatocellular carcinoma (HCC) is still the third leading cause of cancer-related death worldwide. M1 macrophages (Mφ) play a key role in host antitumor defenses in HCC. In our study, CD14 + cells were isolated from the peripheral blood of four groups of HCC patients (group-1, patients with stage 0 HCC; group-2, patients with stage A HCC; group-3, patients with stage B HCC; and group-4, patients with stage C HCC) and characterized phenotypically. Then, CD14 + cells from group-2 and group-3 HCC patients were induced to polarize and tested for their antitumor abilities in a chimera model of HCC patients. Human HCCs (HepG2 solid tumors) grew in a chimera model of group-3 patients (group-3 HCC chimeras) but not in a chimera model of group-2 patients (group-2 HCC chimeras). In response to HCC antigens, the majority of CD14 + cells from group-2 patients (group-2 CD14 + cells) switched to the M1 phenotype (IL-12 + IL-10 − iNOS + cells), whereas the majority of CD14 + cells from group-3 patients (group-3 CD14 + cells) did not switch to the M1 phenotype and continued to express M2b phenotypic properties (IL-12 − IL-10 + CCL1 + iNOS − cells). Group-3 CD14 + cells showed M1Mφ polarization after treatment with CCL1 antisense oligodeoxynucleotide (ODN). Therefore, our study indicates that anti-HCC defenses of group-3 HCC chimeras are improved after CCL1 antisense ODN treatment.